Arte e natureza: o uso de pigmentos naturais na prática artística e educacional - Bannach, Cássia Lindolm [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The object of study of this work will be the relation between Art and Nature, observed in the use of natural pigments in the Visual Arts, whose title is ART AND NATURE: The use of natural pigments in artistic and educational practice; The study will focus on the investigation of how alternative and unconventional materials can be used in school space as a multidisciplinary tool that involves questions of creativity, sustainability and the environment, and for the artist a way to seek inspiration and interact with nature, obtaining A unique art. The main objective of the research will be the demonstration of the viability of the use of natural pigments, correlating Art and Nature, issues of sustainability and transdisciplinarity. The methodology adopted will be applied research, with exploratory, experimental and participatory research objectives. The results will validate the search

O presente trabalho teve como objetivo estudar as correlações entre Arte e Natureza, por meio da utilização de pigmentos naturais. O estudo investigou o uso de pigmentos naturais como materiais alternativos e não convencionais no espaço escolar, as atividades com pigmentos funcionaram como uma ferramenta multidisciplinar em questões que envolveram criatividade, sustentabilidade e meio ambiente. No ponto de vista do artista o estudo mostrou que a interface arte e natureza é uma forma do artista buscar inspiração e uma alternativa para o artista obter uma arte única. A pesquisa também mostrou a viabilidade econômica, social e educacional com o uso de pigmentos naturais, correlacionados a Arte e Natureza, questões de sustentabilidade e transdisciplinaridade
Keywords: Natureza (Estetica); Pigmentos; Abordagem interdisciplinar do conhecimento